Determination of concentration of lead in the soil of Marren Alsaleeb dam and their relationship with chemical properties - هيفا, سوسن; نيصافي , ابراهيم; حداد , محمد (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed to determine the degree of contamination of Marren Alsaleeb dam's soil (Hama - Masyaf) of Lead, studying the physical and chemical properties of soils, and knowing relationship between the total amount of lead and soil properties. Soil samples were collected from two depths (0-20 cm) / (20-40 cm) on dam basin's soil and both sides, Samples were collected from different dimensions of the dam body, ranging in size to a maximum of 3 km. The study indicated that the soils were different textures, Soil degree of interaction (pH) was moderate to alkaline, Soil salinity was within the normal limit, Soils were of good organic content, Results of the research showed that the total of calcium carbonate content was medium to high content. Total amount of lead in the topsoil ranged between (40.7 - 112.51 mg / kg), in the subsoil ranged between (32.81 - 98.37 mg / kg). Lead accumulated in the topsoil in all sites, The highest concentration of lead was in the basin's soil which exceed the critical limit. The results of the research indicated that the lead concentration in the upper part of the dam basin gradually decreased towards the dam body. The results also showed the existence of a positive medium-strength relationship linking the total amount of lead with both the organic matter and the percentage of clay.